L’art de vivre ensemble. Le quotidien des chrétiens et musulmans au temps de la guerre civile algérienne dans les écrits de Christian de Chergé - Pawlicki, Jędrzej (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Collected in the volume L’Invincible espérance, Christian de Chergé’s writingsaddress the theme of mercy in the Christian Bible and in the Koran. De Chergé describedalso the practices of Christian life in a Muslim country. Hence my reflection followed intwo stages: first, I propose to see the theological concepts of the author, anchored in thestudy of biblical and Koranic texts, in the spirit of religious pluralism, and then, to analyzethe modes of living together of Christians among Muslims at the time of rupture. In thissecond part, I am inspired by the rule of Saint Benedict and the work of Michel de Certeauwho perceives daily practices as an act of resistance.